Transformative Digital Leadership for Sustainable Islamic Higher Education: Strategies, Challenges, and Opportunities - Sonia, Nur Rahmi (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The rapid advancement of digital technology has significantly influenced the transformation of Islamic higher education institutions toward sustainability. Transformative digital leadership is essential in guiding innovative and effective changes aligned with sustainable development principles across both academic and administrative domains. This study explores strategies, challenges, and opportunities of transformative digital leadership in supporting sustainability within Islamic higher education. Through a literature review and qualitative analysis, the findings reveal that visionary, inclusive, and adaptive digital leadership enhances collaboration, improves institutional efficiency, and fosters innovation. Effective strategies include strengthening digital competencies among leaders, integrating information technology into teaching and management, and promoting a technology-based organizational culture. However, challenges such as limited technological infrastructure, resistance to cultural change, and inadequate digital literacy among academic communities remain significant barriers. Despite these obstacles, opportunities exist to build collaborative ecosystems, encourage innovation, and accelerate sustainable practices. The study concludes that the success of transformative digital leadership relies not only on mastering technology but also on the ability to drive cultural and organizational change. It is therefore recommended that Islamic higher education institutions invest in digital capacity building, formulate comprehensive transformation policies, and create networks that promote innovation and sustainability.